Blended Learning Design As an Alternative Solution for Limited Face To Face Learning (Unnes Science Education Journal, 2022)
After the Covid-19 emergency period lasted for 1.5 years, there are now Joint Decrees of the Minister of Education and Culture, the Minister of Health, and the Minister of Home Affairs of Indonesia which allow limited face-to-face learning in schools . The implementation rules limit the number of students in the class to only 50% and the duration of study in class is a maximum of 3 hours. The research aims to develop an effective blended learning design as an alternative solution for face-to-face learning in the classroom, especially in science and biology. Blended learning can be applied in 2 strategies, namely flipped classroom and hybrid learning. This research design is reffer to model from Borg & Gall that are including: research and information collecting, planning, develop preliminary from product, preliminary field testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, and dissemination and implementation. The product of this research includes a set of blended learning plan, digital learning material, digital student worksheet, and digital evaluation have good feasibilities and can be implemented in science and biology learning the junior high and senior high school. Therefore, Blended learning can be a solution to overcome limited face-to-face learning in the classroom after the COVID-19 pandemic.